2012
DOI: 10.1111/peps.12012
|View full text |Cite
|
Sign up to set email alerts
|

Work–Family Conflict and Flexible Work Arrangements: Deconstructing Flexibility

Abstract: Workplace flexibility has been a topic of considerable interest to researchers, practitioners, and public policy advocates as a tool to help individuals manage work and family roles. In this study, meta-analysis is used to clarify what is known about the relationship between flexible work arrangements and work-family conflict by deconstructing the flexibility construct. We found that the direction of work-family conflict (work interference with family vs. family interference with work) and the specific form of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
740
7
53

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 725 publications
(828 citation statements)
references
References 106 publications
28
740
7
53
Order By: Relevance
“…Indeed, employers seem to be motivated to offer their workforces greater temporal/spatial flexibility and work-family support in part because they believe doing so will attract and retain valuable employees (Allen et al, 2013). Workplace flexibility is considered an important organizational practice that helps employees effectively manage their work demands and family responsibilities (Allen et al, 2013).…”
Section: Hypothesis 2 (B)mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, employers seem to be motivated to offer their workforces greater temporal/spatial flexibility and work-family support in part because they believe doing so will attract and retain valuable employees (Allen et al, 2013). Workplace flexibility is considered an important organizational practice that helps employees effectively manage their work demands and family responsibilities (Allen et al, 2013).…”
Section: Hypothesis 2 (B)mentioning
confidence: 99%
“…Indeed, employers seem to be motivated to offer their workforces greater temporal/spatial flexibility and work-family support in part because they believe doing so will attract and retain valuable employees (Allen et al, 2013). Workplace flexibility is considered an important organizational practice that helps employees effectively manage their work demands and family responsibilities (Allen et al, 2013). Kattenbach, Demerouti, and Nachreiner (2010) showed that flexibility at workplace allowed 167 German company employees to have more autonomy over their work schedules, thus reducing negative workfamily/family-work spillover.…”
Section: Hypothesis 2 (B)mentioning
confidence: 99%
“…Hence, in contrast to employer perspective on flexibility which tend to perceive flexibility as being instrumental to organizational goals, here flexibility is primarily being instrumental to self-set employee goals. These goals have traditionally been related to work-life balance concerns (Allen et al, 2013), as the literature on flexible work arrangements until recently has been linked to the needs of women and young parents for work arrangements that would suit meeting the demands from work as well as from home (Ferguson et al, 2015). However, recent research has expanded the view of workplace flexibility being primarily useful for women and young parents, to a perspective of flexibility as being available to all employees within an organization, who may have different reasons for using flexibility (Bal, Van Kleef, & Jansen, 2015;Hyman et al, 2005).…”
Section: Employee Perspectives On Workplace Flexibilitymentioning
confidence: 99%
“…Organizations try to become more flexible and adaptable to ever changing economic circumstances (Volberda, 1996; Way et al, 2015), while employees are expected to be more flexible in how they approach their jobs and careers (Hill et al, 2008a). Moreover, employees are increasingly looking for more flexibility in how they balance their work with their personal lives (Allen, Johnson, Kiburz, & Shockley, 2013;Ferguson, Carlson, & Kacmar, 2015), and in how they develop their careers (Moen & Sweet, 2004). Finally, governments across the world have increasingly responded to these trends by declaring flexibility the keyword for the future workforce and workplace (Johnson, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation